Training responses of selected physiological parameters in competitive male cyclists - Abraham, A.; Rombach, S. E. (Medicine & Science in Sports & Exercise, 1998)
Competitive cyclists (N = 8) performed three sets of physiological tests over a seven-month period. Maximal tests evaluated VO2max, ventilatory threshold, maximum heart rate, heart rate at ventilatory threshold, and %VO2max at ventilatory threshold. Submaximal tests evaluated heart rate of VO2 at the end of two intervals with different workloads (150 and 350 watts). Morning resting heart rate was also monitored.